Tinjauan Yuridis Terhadap Perbuatan Melanggar Hukum Atas Harta Kekayaan Yang Dibeli Bersama Oleh WNI Dan WNA Tanpa Ikatan Perkawinan (Studi Putusan Nomor 129/PDT.G/2021/PN BTM) - Cahyarani, Andhini; Aldira Mara Ditta Caesar Purwanto (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Technological advances and globalization have increased interactions between Indonesian citizens (WNI) and foreign nationals (WNA), including those in unmarried relationships. This study analyzes legal protection for Indonesian citizens in disputes over joint property ownership with unmarried foreign nationals, as examined through Batam District Court Decision Number 129/Pdt.G/2021/PN Btm. The research method used is normative juridical, with case, statutory, and conceptual approaches. The results indicate that the Defendant's (WNI) actions do not legally meet the elements of an Unlawful Act (PMH) under Article 1365 of the Civil Code, even though the Plaintiff (WNA) has already entered into a sale and purchase transaction for the house. This dispute is more appropriately classified as a gift without legal basis (onverschuldigde betaling). Legal protection for Indonesian citizens can be provided preventively through written agreements and avoiding nominee practices, as well as repressively by filing an appeal to restore ownership rights based on the certificate.